Insight about Menstrual Cups on Student of the Faculty of Pharmacy and Health Science, Abdurrab University - Febrianita, Yulia; Annisa, Indhy Azzahra Nur (Journal of Health Science and Medical Therapy, 2024)
Menstrual cup is a cup-shaped device used during menstruation that is made from slicone so it is environmentally friendly. Menstrual cups are still not widely accepted in the society and are less desirable than sanitary pads. This study aims to determine the description of knowledge about menstrual cups in students of the Faculty of Pharmacy and Health Sciences, Abdurrab University in 2022. This research method is quantitative research with descriptive design. In this study using cluster random sampling technique so that the number of samples used was 260 students using a questionnaire consisting of 20 questions distributed via googleform. The results of this study showed that the knowledge of female students was in the good category of 175 people (67.3%), 76 people (29.2%) had sufficient knowledge and had less knowledge as many as 9 people (3.5%). The level of knowledge of female students of the Faculty of Pharmacy and Health Sciences, Abdurrab University is good as many as 175 people (67.3%) and it is hoped that female students can increase their knowledge insights and appropriate and sustainable education so that fear and obstacles to using menstrual cups can be overcome.